2004
DOI: 10.4141/p03-202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seeding date and harvest stage on yields and essential oil composition of three cultivars of dill (Anethum graveolens L.) grown in Nova Scotia

Abstract: Experiments were conducted in two locations in Nova Scotia, Canning and Truro, during 2001 and 2002 to determine the effect of seeding date and harvest stage on productivity and composition of essential oil from Anethum graveolens L. ‘Mesten, Dukat’ and ‘Hercules’. Delayed seeding generally reduced yields and altered the concentration of some essential oil components. Both dill seed and dill weed oil from this study had compositions similar to commercially available oil and reported dill oil compositions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
1
9
1
Order By: Relevance
“…Dill weed EO is predominantly composed of carvone (41.6%) and limonene (27.4%), followed by dill ether (9.2%). Current study results were in accordance with previous reports [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…Dill weed EO is predominantly composed of carvone (41.6%) and limonene (27.4%), followed by dill ether (9.2%). Current study results were in accordance with previous reports [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…The influence of harvest time on fresh and dry weight of flowering heads may be a result of available day-length, temperature, and sunlight accumulations [30]. Indeed, previous research has demonstrated significant effects of harvest time on oil yields and composition in other plant species, e.g., dill (Anethum graveolens) [31,32], Dracocepholum moldavica) and Origanum majorana [33], lemongrass (Cymbopogon flexuosus) [34], spearmint ('Scotch' spearmint [Mentha × gracilis Sole]) and 'Native' spearmint [M. spicata L.]) [35].…”
Section: Fresh and Dry Biomass Yieldsmentioning
confidence: 99%
“…on many factors, e.g. cultivar, climatic and soil condition, fertilization, seeding date, harvest date, weed competition, plant disease, management practices, stage of growth, geographical variation, water stress, wind of higher velocity, storage, and processing conditions (Bowes et al, 2004;El-Zaeddi et al, 2016;El-Zaeddi et al, 2017). It was also observed that plants grown at low density had lower proportion of steam and leaf tissue and more extensive development of umbellate fruiting structures compared to plants grown at high density (El-Zaeddi et al, 2017).…”
Section: Yieldmentioning
confidence: 97%
“…The first type could be extracted from weed (0.09 to 0.34 mL 100 g -1 of fresh mass) and the second from mature seeds (0.2 and 4.6 mL 100 g -1 ). The essential fruit oil consists mainly of limonene and carvone, whereas weed oil includes α-phellandrene, myristicin and apiole (Bowes et al, 2004). It is well-known that the specific aroma of plant is determined by the concentration and composition of essential oils (El-Zaeddi et al, 2016) and is formed by complex of chemical substances, such as: alcohols, ketones, aldehydes, esters, terpenes and lactones (El-Zaeddi et al, 2017).…”
Section: Essential Oil Constituentsmentioning
confidence: 99%
See 1 more Smart Citation